2021
DOI: 10.1161/circoutcomes.120.007800
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Managed Care May Be Related to Improved Prognosis for Acute Myocardial Infarction Survivors

Abstract: Background: Mortality following discharge in myocardial infarction survivors remains high. Therefore, we compared outcomes in myocardial infarction survivors participating and not participating in a novel, nationwide managed care program for myocardial infarction survivors in Poland. Methods: We used public databases. We included all patients hospitalized due to acute myocardial infarction in Poland between October 1, 2017 and December 31, 2018. We excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…The 1-year all-cause mortality was significantly statistically lower in study group when compared with patient without MC-AMI. These data confirmed the results obtained in other centers that run or analyzed the MC-AMI program [26,27,28,29,30]. In the two largest nation-wide analyses of effectivness of MC-AMI, participating in the program was related with improved prognosis [26,27].…”
Section: One-year Follow-upsupporting
confidence: 83%
“…The 1-year all-cause mortality was significantly statistically lower in study group when compared with patient without MC-AMI. These data confirmed the results obtained in other centers that run or analyzed the MC-AMI program [26,27,28,29,30]. In the two largest nation-wide analyses of effectivness of MC-AMI, participating in the program was related with improved prognosis [26,27].…”
Section: One-year Follow-upsupporting
confidence: 83%
“…This might have been associated with worse diagnostic in Poland, mainly based on echocardiography and coronary angiography, and rarely enriched with intravascular imaging and cardiac magnetic resonance. Also, this might be related to poor long-term monitoring of patients with acute coronary syndrome [25], and as was shown, patients with proper follow-up characterized better outcomes in Poland [26]. In our study, the 12-month outcomes showed a trend to be worse for MINOCA patients in 2020, with male sex (HR 2.09, 95% CI 1.43-3.05), age (HR 1.07, 95% CI 1.05-1.09), chronic kidney disease (HR 2.07, 95% CI 1.27-3.38), peripheral artery disease (HR 1.96, 95% CI 1.10 -3.47), and STEMI at admission (HR 2.10, 95% CI 1.17-3.79) as the poorest prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In patients covered by the new system, the rate of participation in outpatient cardiac rehabilitation was six times greater than in patients who were not. A smaller but notifiable evident was recorded for the participation rate in the inpatient cardiac rehabilitation that was higher by about 53% [58]. Earlier experience from an experimental study carried out in Polish CHD and high-risk patients suggested that a managed, comprehensive cardiac prevention and rehabilitation program is an effective lifesaving procedure [59].…”
Section: Secondary Preventionmentioning
confidence: 98%
“…Earlier experience from an experimental study carried out in Polish CHD and high-risk patients suggested that a managed, comprehensive cardiac prevention and rehabilitation program is an effective lifesaving procedure [59]. Analysis of the new system of managed care confirm that improved access to cardiac rehabilitation, along with improved access to cardiac consultations and invasive treatment procedures, might contribute to the 30% lower risk of death, observed within 1 year after hospitalization in patients participating in the new system compared to those who are not [58]. However, no information is available on how much of the effect on mortality could be attributed to the reduction of risk factors.…”
Section: Secondary Preventionmentioning
confidence: 99%